Centre for Business Research, Cambridge: Leximetric Datasets - Labour, Company and Insolvency, 1970-2025 - Deakin, Simon F. (UK Data Service, 2025)
The Cambridge Leximetric Datasets are the product of work carried out at the Centre for Business Research (CBR) in Cambridge, beginning in 2005 when the Centre received funding from the Economic and Social Research Council to carry out a research project on law, development and finance. Further funding from the ESRC, the European Union's FP5 and FP6 programmes, the Isaac Newton Trust, the Cambridge Political Economy Society, the International Labour Organization and the NORFACE consortium made it possible to expand the original datasets to their current state. The most recent iteration of the datasets was supported by the ESRC via its grant to the ESRC Research Centre on Digital Futures at Work, and by the NORFACE consortium grant to the POPBACK project (Populist Backlash, Democratic Backsliding, and the Future of the Rule of Law in Europe). As of December 2023, there are three principal datasets, coding, respectively, for labour laws in 117 countries between 1970 and 2022 (the CBR Labour Regulation Index: CBR-LRI), shareholder protection in 30 countries between 1990 and 2013 (the CBR Extended Shareholder Protection Index: CBR-SPI), and creditor protection in 30 countries between 1990 and 2013 (the CBR Extended Creditor Protection Index: CBR-CPI). In addition, as of April 2025, there is a dataset coding developments in the regulation of platform work in 95 countries between 2016 and 2025 (the CBR Platform Work Index: CBR-PWI). The coding of legal data is carried out using a leximetric coding methodology developed in the CBR and more fully explained in the codebooks which accompany each of the datasets. Taken together, the datasets provide a unique time series which enables researchers and other research users to track changes in labour, company and insolvency law over long periods of time for many countries. A distinguishing feature of these datasets is that all legal sources for the data coding are fully described in the relevant codebooks, thereby assisting transparency, external validity and replicability of results. The ESRC Digital Futures at Work Research Centre is an essential resource for those wanting to understand how new digital technologies are profoundly reshaping the world of work. Digitalisation is a topical feature of contemporary debate. For evangelists, technology offers new opportunities for those seeking work and increased flexibility and autonomy for those in work. More pessimistic visions, in contrast, see a future where jobs are either destroyed by robots or degraded through increasingly precarious contracts and computerised monitoring. While such positive and pessimistic scenarios abound of an increasingly fragmented, digitalised and flexible transformation of work across the globe, theoretical understanding of contemporary developments remains underdeveloped and systematic empirical analyses are lacking. Drawing resources from different academic fields of study, the Centre provides an empirically innovative and international broad body of knowledge that will offer authoritative insights into the impact of digitalisation on the future of work. The Centre is jointly led by the Universities of Sussex and Leeds, supported by leading experts from Aberdeen, Cambridge, Manchester and Monash Universities.